Monitoring of masonry historical constructions: 10 years of static monitoring of the world's largest oval dome - Ceravolo, Rosario; De Marinis, A.; Pecorelli, M. L.; Zanotti Fragonara, Luca (Monitoring of masonry historical constructions: 10 years of static monitoring of the world's largest oval dome, 2017)
This paper presents the analyses conducted on the data acquired by the monitoring system of the “Regina Montis Regalis” Basilica of Vicoforte (Italy) in the decade 2004–2014. The Basilica is a building of great historical, architectural, and structural significance, owing its fame to its impressive masonry oval dome, the world's largest of this shape (internal axes of 37.23 by 24.89 m). The dome-drum system of the Basilica has suffered over the years of significant structural problems, partly due to the settlements of the building induced progressively by newly built masses and also to the sliding of the underground. In 1983, concerns over the severe settlements and cracking phenomena affecting the structure prompted the decision to undertake strengthening interventions. A special hooping system, consisting of 56 tie bars, placed around the oval perimeter of the dome, was thus conceived to limit the crack opening. The monitoring system of the Basilica installed in the early 1980s underwent several renovations, and in 2004, its acquisition procedure was automatized. One hundred twelve instruments, consisting of temperature sensors, crackmeters, load cells, pressure cells, wire gauges, hygrometer, piezometers, and hydrometer, are currently installed on the Basilica. This study is primarily focused on data acquired by the crackmeters, the extensometers along the main axes of dome, and the load cells placed at the ends of the tie bars. The main aim of the reported analysis is to evaluate the possible progression of the cracks on the Basilica, and the structural performance of the strengthening interventions put in place in 1985–1987.